Estudo clínico-epidemiológico da síndrome cardiopulmonar por hantavírus na região de Uberlândia-MG, 2006 - Limongi, Jean Ezequiel (2007)
The first objective of this work was to study aspects epidemiologic, clinical, laboratory and treatment of 23 cases of Hantavirus Cardiopulmonary Syndrome (HCPS) diagnosed in the Uberlândia County, Minas Gerais, Brazil in the period among August of 1998 to December of 2005. All the analyzed parameters were obtained through the medical records of each patient one, filed at the researched hospitals and in the database of the surveillance service county. Fever, dyspnea and myalgia were the symptoms more frequently observed in this casuistry. The most prevalent physical signs were hypotension (65.0%) and tachycardia (65.0%). More common laboratory findings included thrombocytopenia (96.0%), hemoconcentration (83.0%) and leukocytosis (74.0%). Abnormal values of hepatic enzymes and abnormalities in chest radiography were equally frequent. In 55.5% of the patients were required orotraqueal intubation and hemodynamic support. There was statistically significant association between the type of mechanic ventilation used and the survival (p<0.01). Intravenous liquid infusion (p=0.5), as well as the use of drugs for increasing systemic vascular resistance and inotropism (p=0.2) and of corticosteroids (p=0.6), didn't have association with the patients' survival. The present study confirmed the seasonal pattern of HCPS in the Uberlândia region and the involvement of professional groups considered of low infection risk in the transmission cycle of the disease.The second objective was to detect the soroprevalence of antibodies against hantavirus in urban and rural population samples of the municipal district of Uberlândia - MG and to correlate the soroprevalence found to the possible risk factors researched. It was raffled, randomly, 200 inhabitants of the urban zone and 200 of the rural, totaling 400 people. Individual interviews were led to characterize the population with relationship to the demographic and socioeconomic aspects, besides investigating possible factors associated SCPH. It was obtained, for venopuncture, blood samples of 400 inhabitants between 13 and 76 years. The participants survey sera were submitted to indirect ELISA, in the dilution 1:400, seeking to the detection of IgG antibodies for Araraquara hantavirus. General positivity rated 3.0%, being of 2.0% in the urban zone and 4.0% in the rural zone. In the urban zone, there was not statistical significance for the positivity difference for hantavirus in relation to the sex (p=0.43). The mean age of the seropositives participants was higher significantly when compared with those with negative serology (p=0.03). In relation to the activities, exposure and risk indicators for the hantavirus disease, statistically significant association was not observed for none that variables in relation to the positivity. In the rural zone, the positivity difference in relation to the sex was significant (p=0.03). All were of the male sex and with higher age to 40 years. The mean age of participants with positive serology was higher in relation to the seronegatives individuals (p=0.05). Among the activities, exposure and risk indicators associated to the hantavirus disease, only the activity "soil plowing " just showed significant association in relation to the positivity (p=0.02). There was not significant difference among the positivity for hantavirus and dwelling place (urban/rural) (p=0.19). There also was not difference among the means of age of the seropositives individuals of the urban and rural zone (p=1.0). However, the sex of the seropositives individuals was statistically different in those areas (p=0.02).The prevalence of antibodies Araraquara-reagents in inhabitants of Uberlândia-MG demonstrates that the transmission of the hantavirus is not rare, and, once again it is also confirmed in that area, the hypothesis of the existence of oligo or asymptomatic infections.